Penerapan Metode Beyond Center And Circle Time Untuk Meningkatkan Kemandirian Pada Anak Usia Dini - Mutmainah, Mutmainah; , Dr. Nanik Prihartanti, M.Si; , Dra. Wiwien Dinar Pratisti, M. Si (2014)
This study aims to determine the role of educator, strength methods and interactions that occur in the method Beyond Center and Circle Time (BCCT), in increasing independence in early childhood. Beside that, this research is also has aim to knowing how educators apply their learning, how the power of BCCT method, how students undergo a learning process, how to carry out their duties as the principal method of learning BCCT and how interactions between students and teachers during the implementation of the learning using the BCCT. The method used is a qualitative method, in the form of case studies of program evaluation, data collection using interviews and observations. Subjects in this study were all educators and principals play Al Huda groups residing in the district, amounting to 5 Colomadu educators and children are listed as students in group play Al Huda. The conclusions obtained are as follows; role of Educators in running BCCT method is capable of making independent child starts from preparing environmental learning activities, managing learning, evaluation and documentation, to establish communication with the parents and facilitators. BCCT method of learning strength is; flexible method, lead creative educators, make the child independent and according to early childhood learning. Conditions felt by children when learning in centers using the BCCT is; Child happy, excited, more organized and able to communicate with other children . Principal's role in the learning method is BCCT in children autonomous; designing learning model, to control the course of learning, coordinating with educators, policy makers, selection and human resource development educators, as well as to establish communication with educators and parents. Educators and child interaction that exists at the center include; interaction between teachers and students entwined in the form of verbal and non-verbal. The interaction of children and educators at the centers and the interactions that occur when children and educators outside the center .